2018
DOI: 10.1111/eva.12721
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization erodes niche segregation in Darwin's finches

Abstract: Urbanization is influencing patterns of biological evolution in ways that are only beginning to be explored. One potential effect of urbanization is in modifying ecological resource distributions that underlie niche differences and that thus promote and maintain species diversification. Few studies have assessed such modifications, or their potential evolutionary consequences, in the context of ongoing adaptive radiation. We study this effect in Darwin's finches on the Galápagos Islands, by quantifying feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 107 publications
1
76
1
Order By: Relevance
“…7: 191959 on anthropogenic food can be harmful for wildlife (e.g. [46,47]). A more comprehensive understanding of the cues that cause wild animals to engage in interactions with humans is likely to be key in developing preventative measures that not only reduce negative encounters for humans but also potentially lessen the impact of anthropogenic items on wild animal populations.…”
Section: Discussionmentioning
confidence: 99%
“…7: 191959 on anthropogenic food can be harmful for wildlife (e.g. [46,47]). A more comprehensive understanding of the cues that cause wild animals to engage in interactions with humans is likely to be key in developing preventative measures that not only reduce negative encounters for humans but also potentially lessen the impact of anthropogenic items on wild animal populations.…”
Section: Discussionmentioning
confidence: 99%
“…The Galapagos currently hosts 225,000 tourists each year and is home to ~30,000 permanent residents (Walsh & Mena, ). Consequently, in areas with the presence of humans (e.g., towns and areas with high human visitation rates), the natural habitat and diet of endemic species, such as Darwin's finches, have been altered (de León et al., ). In turn, changes in the natural and unnatural diet of Darwin's finches has affected selection on their bill size and shape (Hendry et al., ; de León, Podos, Gardezi, Herrel, & Hendry, ; de León et al., ) and thus might also affect their gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on localities that were studied by de León et al. () because the authors showed that Darwin's finches, such as small and medium ground finches, in areas with human presence preferrentially consumed human‐based food (i.e., crisps, biscuits and rice) over their natural foods salt bush ( Cryptocarpus pyriformis ), smooth‐stemmed tournefortia ( Tournefortia psilostachya ) and thorn shrub ( Scutia spicata ); in contrast, finches in areas without human presence did not forage on human‐based food when given the option. Because diet can influence gut microbiota, we hypothesized that measures of the gut bacterial communities, such as diversity, relative abundance of taxa, and community structure and membership, would differ across a gradient of human disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization has had numerous evolutionary and ecological consequences on the Galápagos (De Leon et al, 2018; Hendry et al, 2006; Sequeira et al, 2016; Tanner Perry, 2007), indicating that human-induced habitat disruption is one of the foremost threats to biodiversity on the islands (Pizzitutti et al, 2017; Quiroga, 2018). Our findings similarly suggest that urbanization has played an important role in the loss of endemic CHS and GAL populations.…”
Section: Discussionmentioning
confidence: 99%